2018
DOI: 10.1186/s13223-018-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Rash induced by enteral vancomycin therapy in an older patient in a long-term care ventilator unit: case report and review of the literature

Abstract: BackgroundOral vancomycin is a first-line treatment for severe Clostridium difficile colitis. Oral vancomycin is perceived to lack systemic absorption or systemic adverse effects; however, a few cases of hypersensitivity to oral vancomycin have been reported, all in hospitalized patients.Case presentationIn the present case, a 66-year-old woman with end-stage neurodegenerative disease residing in a long-term care facility developed a maculopapular rash following treatment with enteral vancomycin for recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…A previous study reported that the risk factors of the systemic absorption of oral vancomycin included renal insufficiency, severe C. difficile infection, high vancomycin dose (>500 mg/day), long-term treatment (>10 days), intensive care unit admission, use of vancomycin retention enema and gastrointestinal inflammation. 32 All 16 patients described in this summary of the published literature had underlying diseases, which was basically consistent with the aforementioned research. Fortunately, except for one patient with serious underlying diseases and a poor prognosis after taking vancomycin orally for a long period of time, 25 all of the other 15 patients achieved good outcomes after stopping vancomycin and/or receiving other treatments.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A previous study reported that the risk factors of the systemic absorption of oral vancomycin included renal insufficiency, severe C. difficile infection, high vancomycin dose (>500 mg/day), long-term treatment (>10 days), intensive care unit admission, use of vancomycin retention enema and gastrointestinal inflammation. 32 All 16 patients described in this summary of the published literature had underlying diseases, which was basically consistent with the aforementioned research. Fortunately, except for one patient with serious underlying diseases and a poor prognosis after taking vancomycin orally for a long period of time, 25 all of the other 15 patients achieved good outcomes after stopping vancomycin and/or receiving other treatments.…”
Section: Discussionsupporting
confidence: 88%
“…Fortunately, except for one patient with serious underlying diseases and a poor prognosis after taking vancomycin orally for a long period of time, 25 all of the other 15 patients achieved good outcomes after stopping vancomycin and/or receiving other treatments. 11,16,19,20,23,24,2734…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Red man syndrome, renal toxicity, and ototoxicity in oral vancomycin are controversial [26][27][28][29]. Detectable serum concentrations of vancomycin were noted after oral administration in dialysis patients, and impaired gastrointestinal mucosa in a stem cell transplant patient [27,30].…”
Section: Discussionmentioning
confidence: 99%